Clinicopathological study of adrenal pheochromocytoma and extra-adrenal paragangliomas with reference to GAPP and PASS scoring systems - Akash Mondal; Moumita Sengupta; Soumya Dey; Anish Kar; Krishnendu Maiti; Debansu Sarkar; Uttara Chatterjee (Indian Journal of Pathology and Microbiology)
Background: The presence of distant metastasis is known to drastically reduce survival of adrenal pheochromocytoma (PH) and extra-adrenal paraganglioma (PGL). Therefore, predicting malignant potential has an immense impact on prognosis. Pheochtomocytoma of adrenal gland scaled score (PASS) and the grading of adrenal pheochromocytoma and paraganglioma (GAPP) score are two histological algorithms used to predict metastatic potential, but neither has been regarded as ‘gold-standard’. Both these scoring systems are yet to be validated. Here, we tried to validate the association of GAPP/PASS scores with disease outcome and strength of association between individual GAPP/PASS parameters with prognosis. Materials and Methods: This was a prospective study comprising 22 pheochromocytomas and eight paragangliomas. GAPP score was calculated in paraganglioma cases, and both GAPP/PASS scores were calculated for pheochromocytomas. Disease outcome was then tallied with risk stratification of the GAPP/PASS scoring system. Succinate dehydrogenase B (SDHB) immunohistochemistry was done in 15 cases to see its impact on prognosis. Results: The common PASS parameters associated with malignancy were ‘high cellularity’, ‘tumor cell spindling’ and ‘extension into adipose tissue’. PASS score showed high sensitivity and negative predictive value but low specificity and positive predictive value. Similarly, GAPP score also showed high sensitivity and negative predictive value but low specificity and positive predictive value. Conclusion: In our study, GAPP/PASS scores successfully segregated tumor with low malignant potential from tumor with higher risk of metastasis, although specificity of GAPP was more than PASS. We also found that addition of objective parameters like SDHB immunohistochemistry may further increase the specificity of the existing scoring system.